リュツォ・ホルム ワンイキ ノ アルベド ブンプ - 中川, 清隆; ナカガワ, キヨタカ; Nakagawa , Kiyotaka (1997)
P(論文) NOAA/AVHRRデータから狭帯域地表面アルベドを推定する方法が開発され, 南極リュツォ・ホルム湾およびその周辺における1990年の地表面アルベド分布の解析に適用された。その結果, 16枚の地表面アルベド分布図が描かれた。衛星データから推定されたアルベドとオングル海峡上で実測されたアルベドを比較すると, 衛星から推定された狭帯域アルベドは, -4%程度の系統誤差はあるものの, 地上で観測された全波長域アルベドの日平均値とよく一致することが明らかである。当該地域の地表面アルベド分布には特徴的なパターンがあることも明らかである。開水域の海面は5%以下の低いアルベドであるのに対して, 流氷域と定着氷の大部分は60%以上の高いアルベドである。定着氷のアルベドはリュツォ・ホルム湾の西側部分よりも東側部分で低く, 特に, 宗谷海岸沖では40%以下である。南極大陸の氷床は80%以上の著しく高いアルベドを持つ。 A method has been developed for estimating the filtered narrow band surface albedo with NOAA/AVHRR data, and has been applied to analysis of the surface albedo distribution in Lutzow-Holm Bay and its neighborhood, Antarctica, in 1990. As a result, 16 maps of the surface albedo distribution have been drawn. From a comparison of the albedos inferred from satellite data with those actually observed in Ongul Strait, it is clear that the satellite-inferred, filtered narrow band albedos agree well with the daily means of ground-observed, unfiltered broad band albedo, despite systematic errors of about -4%. It is also clear that there is a characteristic pattern of surface albedo distribution in this area; the open sea has very low albedo of less than 5%, whereas most of the compact pack ice and fast ice has a high albedo of more than 60%. The albedo is lower in the eastern part of Lutzow-Holm Bay than in the western part; especially off the Soya Coast it is less than 40%. The ice sheet of Antarctica has a remarkably high albedo of more than 80%. departmental bulletin paper